Comparative Efficacy of Resilience Training and Acceptance and Commitment-Based Training on Happiness in Employees of Shiraz Oil Subsidiaries - Pegah Adiby Parsa; Naser Amini; Khosro Ramezani; Mohammad Behroozi (Iranian Journal of Educational Research, 2025)
Objective: The primary objective of the current investigation was to evaluate the comparative efficacy of resilience training versus acceptance and commitment-based training on the happiness of employees affiliated with Shiraz oil subsidiaries. Methods: This research was characterized as applied in nature regarding its aims and was grounded in a quasi-experimental design featuring a pre-test and post-test framework inclusive of a control group. The statistical population for this inquiry encompassed all employees working within the oil subsidiaries in Shiraz during the year 2022. A total of 75 employees meeting specific criteria were selected via convenience sampling and subsequently assigned to three distinct groups (first experimental group: 25 individuals; second experimental group: 25 individuals; control group: 25 individuals). The first experimental cohort underwent training in a resilience therapy program, while the second experimental cohort received instruction in an acceptance and commitment therapy program, with the control group remaining devoid of any targeted intervention. Data collection was conducted utilizing the happiness questionnaire. Results: The findings revealed that the mean happiness score among participants in the control group exhibited a statistically significant difference when juxtaposed with the mean scores of both the acceptance and commitment training group and the resilience training group, in addition to a significant disparity being noted between the two training groups themselves. Conclusions: It can be asserted that the differential impact of the acceptance and commitment training methodology on the happiness of the subjects was statistically significant in comparison to the resilience training approach. Specifically, the pronounced influence of acceptance and commitment training on participants' happiness was found to surpass that of resilience training.